Performance evaluation of substrate intergrated waveguide band-stop filters - Tan, Gan Siang (2015)
This thesis presents the findings of the research work done on the evaluation and performance of substrate integrated waveguide (SIW) band-stop filters. The conventional waveguide has the advantages of low-insertion losses and high Q in microwave communication systems but their physical sizes of rectangular waveguides are large. The introduction of substrate integrated waveguide with similar properties of low insertion loss that can be integrated with planar circuits fulfill the requirement of microwave communication systems. Many researches have carried out detail research work on SIW band-pass filters but not many researches have spent enough time on the research of performance of SIW band-stop filters. In the construction of SIW band-stop filters, resonators feature significantly to realize the structure. Resonators can be constructed from closed sections of SIW. Circular and radial shape cavity resonators are proposed to design the SIW band-stop filters. The SIW band-stop filters are designed by coupling the cavity resonator to the SIW line. The effects on the variation of parameters value of each type of resonators are investigated. CST microwave studio is used for all the simulation work in this research. The designs of the SIW band-stop filters have been realized by using standard PCB process. The measured results are found to be in consistent to the simulated results. The dual-radial cavity resonators SIW band-stop filter has shown enhanced performance in 9GHz band-stop response with a high stopband attenuation level and provide better roll-off of 0.15dB/MHz. These provide better frequency selectivity as compared to the rectangular cavity resonator in the previous research work. This band-stop filter can be used to provide better signal rejection in the X-band.